The Effect of Adding Tea Dregs on The Growth of Brown Oyster Fungus (Pleurotus cystidiosus) on Sawdust Planting Media - Purba, Agnes Lidya Syahtari; Sarjani, Tri Mustika; Jayanthi, Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The aim of the research was to determine the effect of adding tea dregs on the growth and the effective composition of tea dregs on the growth of brown oyster mushrooms (Pleurotus cystidiosus) on sawdust planting media. The type of research is quantitative with an experimental method using a Non-Factoral Completely Randomized Design (CRD) with 5 treatments and 4 replications. Data analysis in the study used parametric tests, namely the Anova test and LSD test as well as non-parametric tests, namely the Kruskal Wallis test and the Mann-Whitney test with SPSS. The results showed a significant effect on mycelium growth (Sig 0.014), number of fruit bodies (Sig 0.016), fruit stalk length (Sig 0.017), wet weight of harvest (Sig 0.000) and a significant effect on the age at which fruit bodies emerged (Sig 0.045) and had no significant on the diameter of the fruit cap (Sig 0.088) of brown oyster mushroom (Pleurotus cystidiosus). The best treatment for each observation parameter was mycelium growth in treatment P4 (19.3938 cm), age of emergence fruit bodies in treatment P0 (34.5 days), number of fruit bodies in treatment P4 (5.375), diameter of fruit cap in treatment P0 (12.3 cm), fruit stalk length in treatment P4 (10 cm), and wet harvest weight in treatment P4 (91 grams). The most effective treatment for the growth of brown oyster mushrooms ((Pleurotus cystidiosus) is P4 treatment with 25% (375 grams of Tea Dregs + 75% (1,125 grams of Swadust).